2015
DOI: 10.1080/2162402x.2015.1041701
|View full text |Cite
|
Sign up to set email alerts
|

Role of natural killer cell subsets and natural cytotoxicity receptors for the outcome of immunotherapy in acute myeloid leukemia

Abstract: In a phase IV trial, 84 patients (age 18–79) with acute myeloid leukemia (AML) in first complete remission (CR) received cycles of immunotherapy with histamine dihydrochloride (HDC) and low-dose human recombinant interleukin 2 (IL-2) for 18 months to prevent leukemic relapse. During cycles, the treatment resulted in expansion of CD56bright (CD3−/16−/56bright) and CD16+ (CD3−/16+/56+) natural killer (NK) cells in the blood along with increased NK cell expression of the natural cytotoxicity receptors (NCRs) NKp3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 48 publications
5
54
0
Order By: Relevance
“…A phase 3 clinical trial using low-dose interleukin-2 combined with histamine dihydrochloride as maintenance therapy for AML demonstrated improved leukemia-free survival compared with no maintenance, an effect that was associated with peripheral blood NK cell expansion and upregulation of the activating natural cytotoxicity receptors NKp30 and NKp46, suggesting that NK cell activation against AML likely contributed to the observed survival benefit. 34,35 Our results suggest that an alternative approach to prevent AML relapse may be to therapeutically enhance the expression of activating NKRLs on residual AML blasts or to reduce inhibitory NKRL signaling, thereby swaying the balance of NK cell signaling toward a more activating pattern. Rohner and coworkers reported that azacitidine upregulated ULBP1 expression on AML H60 blasts when used in combination with interferon-g, resulting in improved sensitivity to NK-mediated killing via NKG2D signaling.…”
Section: Discussionmentioning
confidence: 92%
“…A phase 3 clinical trial using low-dose interleukin-2 combined with histamine dihydrochloride as maintenance therapy for AML demonstrated improved leukemia-free survival compared with no maintenance, an effect that was associated with peripheral blood NK cell expansion and upregulation of the activating natural cytotoxicity receptors NKp30 and NKp46, suggesting that NK cell activation against AML likely contributed to the observed survival benefit. 34,35 Our results suggest that an alternative approach to prevent AML relapse may be to therapeutically enhance the expression of activating NKRLs on residual AML blasts or to reduce inhibitory NKRL signaling, thereby swaying the balance of NK cell signaling toward a more activating pattern. Rohner and coworkers reported that azacitidine upregulated ULBP1 expression on AML H60 blasts when used in combination with interferon-g, resulting in improved sensitivity to NK-mediated killing via NKG2D signaling.…”
Section: Discussionmentioning
confidence: 92%
“…Table 1 provides information about the prior induction and consolidation chemotherapy. Further patient characteristics are accounted for in previous publications [17,18,27]. In this single-armed multicenter phase IV study, patients received 10 consecutive 21-d cycles of HDC and low-dose IL-2 for 18 months or until relapse or death using a regime identical to that employed in a previous phase III trial [28].…”
Section: Clinical Trial Patients Study Design and Objectivesmentioning
confidence: 99%
“…The sensitivity of AML cells to the anti-leukemic activity of cytotoxic lymphocytes such as T cells and NK cells [6][7][8][9][10] along with the purported role of these immune effector cells in the surveillance of leukemic cells [11,12] have inspired the development of strategies to boost cellular immunity in the post-consolidation phase for relapse prevention [13][14][15][16]. The NOX2 inhibitor histamine dihydrochloride (HDC) in conjunction with the T and NK cell activating cytokine interleukin-2 (HDC/IL-2) is approved in AML for relapse prevention in Europe, and recent studies imply that aspects of T and NK cell immunity are relevant to the clinical efficiency of this combinatorial immunotherapy [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…After this work has been submitted, two additional reports from the Hellstrand group independently described an expansion of CD56 bright CD16 neg cells in HDC plus IL-2 treated AML patients [46, 47], but the CD56 bright CD16 low cells were not separately investigated in these studies. Furthermore, somewhat higher intensities of expression of the NCR NKp30 and NKp46 were observed after 3 weeks of treatment and the data supported that a high expression of NKp30 and NKp46 before and during therapy in older patients is a predictor of leukemia-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%